Renal function: sodium balance - Briffa, Jessica (Henry Stewart Talks, 2024)
Solute reabsorption, Active sodium reabsorption, Secondary active transportation of solutes with sodium, Glucose titration curve, Renal regulation of acid-base balance, Sodium balance, Water distribution in the body, Aldosterone mediated sodium reabsorption